2016
DOI: 10.2174/1566524016666151222150024
|View full text |Cite
|
Sign up to set email alerts
|

DREADD in Parvalbumin Interneurons of the Dentate Gyrus Modulates Anxiety, Social Interaction and Memory Extinction

Abstract: Parvalbumin (PV)-positive interneurons in the hippocampus play a critical role in animal memory, such as spatial working memory. However, how PV-positive interneurons in the subregions of the hippocampus affect animal behaviors remains poorly defined. Here, we achieved specific and reversible activation of PV-positive interneurons using designer receptors exclusively activated by designer drugs (DREADD) technology. Inducible DREADD expression was demonstrated in vitro in cultured neurons, in which co-transfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 58 publications
(63 reference statements)
9
74
1
Order By: Relevance
“…Moreover, PV-positive GABAergic interneurons are closely linked to fear memory [27], which is also supported by our previous study [13].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, PV-positive GABAergic interneurons are closely linked to fear memory [27], which is also supported by our previous study [13].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, hippocampal PV GABAergic interneurons have been implicated in anxiety and social behaviors (Çalışkan et al, ; Sun et al, ; Wöhr et al, ). Activation of these neurons in the vHip of mice induced anxiolytic effects in the EPM and impaired social behavior (Zou et al, ), while PV KO mice have been shown to display significant deficits in social interaction and serve as a model for autism spectrum disorders (Wöhr et al, ). Moreover, a rat model of PTSD displayed anxiety‐like behavior in the EPM and LOF, accompanied by significant decreases in glutamic acid decarboxylase (GAD)‐67, a marker of GABAergic neurons, and PV immunoreactivity (Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At a neurochemical level, anxiety is correlated with dysfunctions in hippocampal inhibitory interneuron network activity (Engin & Treit, ; Kalueff, ). For instance, selective stimulation of parvalbumin (PV)‐expressing GABAergic interneurons in the DG, using designer receptors exclusively activated by designer drugs (DREADDs), reduced anxiety and promoted social interaction behavior (Zou et al, ). Meanwhile, recent studies of somatostatin (SST)‐expressing GABAergic neurons in the DG have reported their involvement in memory formation during aversive stimuli (Stefanelli et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus plays key roles in regulating emotional behavior and stress reactivity via its abundant neural connections with limbic structures that convey emotionally salient information from the environment. It has been shown to contribute to the regulation of anxiety‐like behavior (Bannerman et al, ; Bertoglio et al, ; Engin & Treit, ; Gray & McNaughton, ; McNaughton & Gray, ; Moser & Moser, ) as well as aggression (Ely, Greene, & Henry, ; Kolb & Nonneman, ), sociability (Felix‐Ortiz & Tye, ; Hitti & Siegelbaum, ; Maaswinkel, Baars, Gispen, & Spruijt, ; Maaswinkel, Gispen, & Spruijt, ; Stevenson & Caldwell, ; Zou et al, ), and reactive coping in the Forced Swim Test (FST; West, ). Our prior work with the selectively bred HR/LR rats has demonstrated marked differences across all of these behavioral domains, with LR rats (compared to HRs) generally displaying higher levels of anxiety‐like behavior (Clinton et al, , ; Perez et al, ; Stead et al, ; Turner et al, ), low aggression (Kerman et al, ), less interest in sex (Cummings, Clinton, Perry, Akil, & Becker, ) and social interaction (Cohen et al, ), as well as reactive coping (increased immobility) in the FST (Clinton, Watson, & Akil, ; Garcia‐Fuster et al, ; McCoy et al, ).…”
Section: Discussionmentioning
confidence: 99%